Oral-facial-digital syndrome type I. Importance of the skin manifestations. - Cambiaghi, S.; Pistritto, G.; Cavalli, R.; Dellepiane, R.M.; Mastrangelo, M. (European Journal of Pediatric Dermatology, 2018)
The oral-facial-digital syndrome type I is a rare, inherited, polymalformation disorder affecting the female sex. As suggested by its name, the main alterations of the syndrome affect the oral mucosa, the face, the fingers of the hands and the toes. The characteristic skin manifestations, when present, are a clue to the diagnosis. They consist of congenital hypotrichosis and multiple milia. The latter affect the face and head and regress with pinhead atrophic residua. A paradigmatic family case of oral-facial-digital syndrome type I, whose skin manifestations led to the right diagnosis is here reported.